PENGARUH LAMA PENYULINGAN SECARA KERING PADA KONDISI VAKUM TERHADAP RENDEMEN DAN SIFAT FISIKO-KIMIA RESIDU DAMAR MATA KUCING - Bambang Wiyono; Kurnia Sofyan; Dedeh Kurniasih; Poedji Hastoeti (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
Dammar resin of Shorea javanica which its essential oil has been isolated can still be used for industrial purposes. Relating to this, the objective of the research is to investigate the effect of a vacuum dry distillation time on yield and the physico-chemical properties of dammar residue.A vacuum dry distillation technique of dammar was carried out at a pressure of 0.06 Pa, a temperature of 65 - 85°C for 0.5, 1, 1.5, 2, and 2.5 hours, respectively. Each of distilling times was triplicated. To see the effect of distilling time on the yield and properties of dammar residue, the data were analysed by a factorial completely randomized design procedure, and their different means values were tested with Tukey's procedure. The relationship between distilling time and the yield or its physico-chemical properties of dammar residue was analysed with a polynomial orthogonal regression in a SAS package.The results showed that distilling time gave a highly significant effect on yield, softening point, ash content, iod number, acid number and saponification number of dammar residue, except for unsoluble matter in toluene. The increase in distilling lime tent to decrease in the yield and acid number of dammar residue, but it also tent to increase in softening point, ash content, iod number, saponification number and unsoluble matter in toluene. Moreover, distilling time of 2.5 hours is the optimum time to give the highest values of softening point and iod number, but with the lowest value of acid number. Polynomial orthogonal analysis revealed that there were relationship between distilling lime and yield of dammar residue and its properties with a highly significance.Compared to Indonesian National Standard for dammar, dammar residue has not met the requirement for softening point, acid number and ash content criteria. To meet the requirement, it was suggested to increase the pressure in the vacuum dry distillation process with a proper condentation for this pressure.